Finders keepers - Will 1904-; Nicolas 1911-1973. (San Diego Harcourt Brace Jovanovich, 1989)
Two dogs each claim a bone they have found and ask passersby for help in deciding ownership.
"Voyager books."
"Winner of the Caldecott medal."
Keywords: Dogs -- Fiction